The Multifactorial Origin of Respiratory Morbidity in Patients Surviving Neonatal Repair of Esophageal Atresia - Fragoso, Ana Catarina; Tovar, Juan A. (Frontiers in Pediatrics, 2014)
Esophageal atresia with or without tracheoesophageal fistula (EA±TEF) occurs in 1 out of every 3000 births. Current survival approaches 95% and research is therefore focused on morbidity and health-related quality of life issues. Up to 50% of neonates with EA±TEF have one or more additional malformations including those of the respiratory tract that occur in a relatively high proportion of them and particularly of those with VACTERL association. Additionally, a significant proportion of survivors suffer abnormal pulmonary function and chronic respiratory tract disease. The present review summarizes the current knowledge about the nature of these symptoms in patients treated for EA±TEF, and explores the hypothesis that disturbed development and maturation of the respiratory tract could contribute to their pathogenesis.